2x-2y+5z-2x-y+3z=

Simple and best practice solution for 2x-2y+5z-2x-y+3z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-2y+5z-2x-y+3z= equation:


Simplifying
2x + -2y + 5z + -2x + -1y + 3z = 0

Reorder the terms:
2x + -2x + -2y + -1y + 5z + 3z = 0

Combine like terms: 2x + -2x = 0
0 + -2y + -1y + 5z + 3z = 0
-2y + -1y + 5z + 3z = 0

Combine like terms: -2y + -1y = -3y
-3y + 5z + 3z = 0

Combine like terms: 5z + 3z = 8z
-3y + 8z = 0

Solving
-3y + 8z = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8z' to each side of the equation.
-3y + 8z + -8z = 0 + -8z

Combine like terms: 8z + -8z = 0
-3y + 0 = 0 + -8z
-3y = 0 + -8z
Remove the zero:
-3y = -8z

Divide each side by '-3'.
y = 2.666666667z

Simplifying
y = 2.666666667z

See similar equations:

| 5cosx+6cosx-8=0 | | 3^14k7/2^19 | | 2(3x+1)=4(x+5) | | P^2+20p-3500=0 | | 5(2+1)=50 | | 0.71428571y-15=5y+30 | | 5(10x+1)=12 | | 8-3x=-x-2 | | 3n^2-3n-9=0 | | n^2+16n-76=0 | | 54=43+v | | 4x^3-1/x^2 | | 2k^2+6k-1=0 | | 2Y=-6x-5/3 | | 3t+5=14 | | 6/104 | | 28-y=13m | | 3(c+2)=-15 | | (3x+41)+(4x+16)+(5x-12)+(2x+100)+(6x+15)=360 | | 3a-1+8=-8a+7 | | ((1/3a)-3)((1/3a)-3) | | n^2-7=6n | | ((1/3a)-3)^2 | | 3606=2x+x | | 12x+12-4x+4=40 | | b^2+30=11b | | X/8=76 | | 0.5(0.26+9x)=5.2x | | p^2-8p=-7 | | y=-5x^3-5x^2+60x | | 4/5g=1/4 | | mx/9=9 |

Equations solver categories